2022
DOI: 10.35371/aoem.2022.34.e33
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between shift work and non-alcoholic fatty liver disease among male workers in the steel manufacturing company of Korea: a cross-sectional study

Abstract: Background Circadian rhythm disturbance caused by shift work has adverse effects on the metabolic homeostasis of the liver. Disruption of the metabolic homeostasis of the liver causes fat accumulation in the liver. The aim of this study was to investigate the correlation between shift work and non-alcoholic fatty liver disease (NAFLD) among male workers in the steel manufacturing industry of Korea. Methods Based on medical examination data collected in June 2020, 2,511 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…In our study, we found a high prevalence of NAFLD among security guards working in rotating shifts, with 76.1% affected. This prevalence is notably higher compared to similar studies conducted by Kiseok et al in 2022 (44.5%) and Zhang et al in 2020 (33.7%) among shift workers in steel plants in Korea and China, respectively [ 26 , 19 ]. The latest prospective analysis of 281,280 UK Biobank participants reports that workers who occasionally worked night shifts were 1.12 times more and individuals with usual or permanent night shifts had a 1.27 times higher risk of developing (NAFLD), and this association remained significant irrespective of genetic predisposition to NAFLD, indicating that night shift work is associated with an increased risk of incident of NAFLD [ 27 ].…”
Section: Discussioncontrasting
confidence: 53%
“…In our study, we found a high prevalence of NAFLD among security guards working in rotating shifts, with 76.1% affected. This prevalence is notably higher compared to similar studies conducted by Kiseok et al in 2022 (44.5%) and Zhang et al in 2020 (33.7%) among shift workers in steel plants in Korea and China, respectively [ 26 , 19 ]. The latest prospective analysis of 281,280 UK Biobank participants reports that workers who occasionally worked night shifts were 1.12 times more and individuals with usual or permanent night shifts had a 1.27 times higher risk of developing (NAFLD), and this association remained significant irrespective of genetic predisposition to NAFLD, indicating that night shift work is associated with an increased risk of incident of NAFLD [ 27 ].…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies on the association between the duration of shift work and NAFLD outcomes reported inconsistent findings. 19,33,34 Conversely, our findings revealed that shift work durations of 10-20 years and fewer than 10 years were risk factors for NAFLD in healthcare and nonhealthcare shift workers, consecutively, but a long duration (>20 years) of shift work was specifically a protective factor for e-LAP in healthcare personnel. The differences between our results and those of previous studies could be explained by the following possible explanations: the workload of shift workers in Thailand, particularly healthcare personnel, decreased as the duration of shift work increased; or our biological clocks can be adapted to the shift work schedules as time passes.…”
Section: The Associations Of Shift Work With Nafld and Liver Enzyme A...mentioning
confidence: 46%
“…The flow rate of eluent (distilled water) was 0.5 mL/min, and the column temperature was kept at 25 °C. The column was calibrated with a set of dextran standards (5,12,25,80,150,270,410,670, and 1400 kDa). The oat β-glucan sample and dextran standards were dissolved in 0.01 M ammonium acetate and filtered through a 0.45 μm Millipore filter.…”
Section: Composition Analysis Of Oat β-Glucanmentioning
confidence: 99%
“…Recently, it was found that there was a positive association between shift work and NAFLD among Chinese rail workers, 10 UK Biobank participants, 11 and Korean male workers in a steel manufacturing company. 12 Animal studies have revealed that circadian disruption can be harmful to liver health. Kettner et al reported that circadian disruption could induce NAFLD and hepatocellular carcinoma in wild-type mice.…”
Section: Introductionmentioning
confidence: 99%